Parallel randomized controlled feasibility trials of the “Active Brains” digital intervention to protect cognitive health in adults aged 60–85 - Essery, Rosie; Pollet, Sebastien; Bradbury, Katherine; Western, Max J.; Grey, Elisabeth; Denison-Day, James; Smith, Kirsten A.; Hayter, Victoria; Kelly, Joanne; Somerville, Jane; Stuart, Beth; Becque, Taeko; et al. (Frontiers in Public Health, 2022)
Introduction Multidomain interventions to address modifiable risk factors for dementia are promising, but require more cost-effective, scalable delivery. This study investigated the feasibility of the ‘Active Brains’ digital behavior change intervention and its trial procedures. Materials and Methods Active Brains aims to reduce cognitive decline by promoting physical activity, healthy eating, and online cognitive training. We conducted 12-month parallel-design randomized controlled feasibility trials of ‘Active Brains’ amongst ‘lower cognitive scoring’ (n=180) and ‘higher cognitive scoring’ (n= 180) adults aged 60-85. Results We collected 67.2% and 76.1% of our primary outcome (Baddeley verbal reasoning task) data for the ‘lower cognitive score’ and ‘higher cognitive score’ groups, respectively. Usage of ‘Active Brains’ indicated overall feasibility and satisfactory engagement with the physical activity intervention content (which did not require sustained online engagement), but engagement with online cognitive training was limited. Uptake of the additional brief telephone support was higher in the ‘lower cognitive score’ trial. Preliminary trends in the primary outcome data may indicate a protective effect of Active Brains against cognitive decline in both trials requiring further investigation in fully-powered trials. Discussion Findings confirmed the feasibility of ‘Active Brains’ and identified minor modifications to procedures, particularly to improve online primary-outcome completion. These findings warrant further investigation of Active Brains to determine its efficacy in protecting cognitive performance amongst adults aged 60-85 with varied levels of existing cognitive performance.